Networks and learning: communities, practices and the metaphor of networks - Chris Jones (Association for Learning Technology, 2004)
This article argues that the use of the network metaphor can link together various different aspects of research into the use of advanced learning technologies based on computer networks. The idea of networked learning has become commonplace as an alternative to e-learning that stresses the interaction of learners, tutors and resources through networks. The arguments put in this article are firstly that learning technology needs to take account of the wider debate about networks and secondly that research in this field needs to address the theoretical and practical issues raised by advances in the field of networks. A third point is that the idea of the network acts as a powerful metaphor even if we are able to discount any particular theory generated in its support. The network metaphor can act as a unifying concept allowing us to bring together apparently disparate elements of the field. Networks are an important issue in the study of learning using advanced technologies and they speak to some of the central issues in learning theory such as virtual communities and communities of practice.